Krüppel-Like Factor 6 Is Required for Oxidative and Oncogene-Induced Cellular Senescence - Sabatino, Maria Eugenia; Castellaro, Andrés; Racca, Ana C.; Carbajosa González, Sofía; Pansa, Maria Florencia; Soria, Gastón; Bocco, Jose Luis (Frontiers in Cell and Developmental Biology, 2019)
KLF6 is a transcription factor involved in the regulation of several cellular processes. Regarding its role in tumorigenesis, KLF6 is considered a tumor suppressor. Numerous reports demonstrate its frequent genomic loss or down-regulation, implying a functional inactivation in a broad range of human cancers. Previous work from our laboratory showed that the down-regulation of KLF6 expression in normal fibroblasts leads to cellular transformation, while its ectopic expression interferes with the oncogenic transformation triggered by activated Ras through a cell cycle arrest. We hypothesize that the growth suppressor activity of KLF6 may involve the induction of cellular senescence thereby helping to prevent the proliferation of cells at risk of neoplastic transformation. Here, we explored the association of KLF6 up-regulation in two different cellular senescence scenarios. We found that KLF6 silencing bypasses both oxidative and oncogene-induced senescence. In this context, KLF6 expression per se was capable to trigger cellular senescence in both normal and tumoral contexts. As such, the findings presented in this report provide insights into a potential mechanism by which KLF6 may play a suppressing role of uncontrolled or damaged cell proliferation.